Sustainable Campus Town Development in Suburban Area of Bangkok, Thailand - Iamtrakul, Pawinee; Raungratanaamporn, I-soon (International Journal of Building, Urban, Interior and Landscape Technology, 2015)
The importance of university establishment is not aimed only increasing the educational level to young generation by providing specific knowledge, professional skills, or enhancing high-level of training facilities in order to raise skills of people for serving national job market, but also indirectly improving local economy and job opportunities for local people who are living nearby area of university. Therefore, it must be planned to meet the goal of urban development and sustaining the quality of life of the people, especially the suburban area of Bangkok, Thailand. Incorporating with the growth of mega city, the establishment of different university should not only consistent with regional planning and development in accordance to National Economic and Social Development Planning scheme, but should be complying with provincial and community development. However, university has been stimulating community development in all dimensions both positive and negative impacts. Urban problematics such as heavy traffic congestion, immigrations, safety and isolation between the “old-liver” and the “new-comer” had been induced in this area. Thus, campus master planning should be designed to create a node of urban intensification with pedestrian friendly environment which will not only encourage more compact development in the neighboring areas, but also provides health, environmental, and economic benefits.